Characterization and Photo-Induced Electrocatalytic Evaluation for BiVO4 Films Obtained by the SILAR Process - Pelissari, Marcelo Rodrigues da Silva [UNESP]; Azevedo Neto, Nilton Francelosi [UNESP]; Camargo, Luan Pereira; Dall’Antonia, Luiz Henrique (Springer Nature, 2021)
BiVO4 is an important semiconductor material that can be applied as a photoanode in several electrochemical systems, using the visible region of the electromagnetic spectrum as an excitation source to charge carrier generation. However, due to the unfavorable charge carrier recombination process, which is an intrinsic property of semiconductor materials, alternative conditions of synthesis and different electrode architecture are fundamental to improving their photoelectrocatalytic activity. In this paper, the construction of a photoanode using BiVO4 films with the monoclinic crystalline structure was successfully obtained by a quick and low-cost process: the Successive Ionic Layer Adsorption and Reaction (SILAR). The characterization of electrodes (5, 10, and 15 SILAR-deposited layers), which was carried out by x-ray diffraction (XRD), Raman spectroscopy, scanning electron microscope (SEM), and UV-Vis spectroscopy diffuse reflectance techniques, showed the efficiency of the SILAR process in the construction and architecture of the FTO/BiVO4 electrode. The FTO/BiVO4 photoanodes constructed have exhibited interesting photoelectrochemical responses, such as high photocurrent density (jph), low resistance to charge transfer (Rct), and high charge carrier density (ND). The photocurrent value obtained for a 5-layer film was 1.95 mA cm−2, twice as large than a 10-layer film (0.97 mA cm−2) and three times greater than a 15-layer film (0.61 mA cm−2). The resistance-to-charge transfer values are in good agreement with the photocurrent density values, where the 5-layer film presented the Rct value of 0.15 kΩ, lower than the other obtained electrodes. Regarding the rhodamine b (RhB) photoelectrodegradation reaction, all electrodes showed good photoelectrocatalytic activity as evidenced by pseudo-first order kinetics constant (kobs) values. Graphical abstract: [Figure not available: see fulltext.]
Keywords: BiVO4; Discoloration; Photoelectrocatalytic activity; Rhodamine b; Semiconductor; SILAR process